Work-related smartphone dependency among young working adults in urban China : an examination of the dependency relations, antecedents, and consequences - Li, Li (2017)
Using smartphones for day-to-day working practices is now common for employees working in many organizations and companies. This dissertation is among the first to apply Media System Dependency (MSD) theory to understand smartphone dependency within a working context. By targeting young working adults in mainland China, this dissertation aims to answer three questions: 1) what kinds of dependency relations that young Chinese workers develop with their smartphones at work; 2) what are the antecedents of these work-related smartphone dependency relations; and 3) what are the consequences of these work-related smartphone dependency relations.